-Identiﬁcation of a novel intestinal phospholipase A2 from annular seabream: Insights into its catalytic mechanism and its role in biological processes. (April 2020) - Smichi, Nabil; Othman, Houcemeddine; Zarai, Zied; Fendri, Ahmed; Abousalham, Abdelkarim
Graphical abstract: Highlights: Diplodus annularis phospholipase PLA2 (IDaPLA2 ) is the first intestinal fish PLA2 . IDaPLA2 present the hallmark of pancreatic sPLA2 and not GIIA-PLA2 . IDaPLA2 showed improved high thermo-stability compared to mammal pancreatic sPLA2 . IDaPLA2 was more active on phospholipid monolayers at high surface pressure. The IDaPLA2 revealed toxicity toward macrophages. Abstract: Phospholipase A2 (PLA2 ) is responsible for the lipid hydrolysis process. Fish PLA2 have warranted renewed interest due to their excellent properties in phospholipid digestion. We report for the first time the catalytic properties of a PLA2 secreted from the intestine of the annular seabream Diplodus annularis (IDaPLA2 ). The refolded IDaPLA2 was purified to homogeneity and showed a molecular mass of around 15 kDa attested by SDS-PAGE and MALDI-TOF analyses. Interestingly, IDaPLA2 revealed higher thermostability compared to mammal pancreatic sPLA2 as it was active and stable at 55 °C with speciﬁc activity of 290 U mg −1 on phosphatidylcholine (PC) as a substrate. Using the lipid monolayer technique, the activity of IDaPLA2 was found to be 21.68, 6.88 and 5.66 mol cm −2 min −1 mM −1 using phosphatidylglycerol (PG), PC and phosphatidylethanolamine (PE) monolayers, respectively, at surface pressures from 20−30 mN m −1 . Interestingly, the interfacial activity of IDaPLA2 measured at higher surface pressures may highlight its ability to penetrate into phospholipid monolayers suggesting its involvement in cell lipid membrane degradation which can explain the cytotoxicity potential towards macrophage. The docking simulation data provided insights into the involvement of some key amino-acids in substrate binding and selectivity. The dynamic simulation proved the high stability of IDaPLA2 . Overall, these results provide original evidence on the involvement of IDaPLA2 into the lipid hydrolysis suggesting it as a potential target in biotechnological applications.